Self‐Reporting Inhibitors: A Single Crystallization Process To Obtain Two Optically Pure Enantiomers. (12th June 2018) - Ye, Xichong; Cui, Jiaxi; Li, Bowen; Li, Na; Zhang, Jie; Wan, Xinhua
Abstract: Collection of two optically pure enantiomers in a single crystallization process can significantly increase the chiral separation efficiency but this is difficult to realize. Now a self‐reporting strategy is presented for visualizing the crystallization process by a dyed self‐assembled inhibitor made from the copolymers with tri(ethylene glycol)‐grafting polymethylsiloxane as the main chain and poly(N 6 ‐methacryloyl‐l ‐lysine) as side chains. When applied with seeds together for the fractional crystallization of conglomerates, the inhibitors can label the formation of the secondary crystals and guide the complete separation process of two enantiomers with colorless crystals as the first product and red crystals as the second. This method leads to high optical purity of d /l ‐Asn⋅H2 O (99.9 % ee for d ‐crystals and 99.5 % for l ‐crystals) in a single crystallization process. It requires a small amount of additives and shows excellent recyclability.